Building Organizational Governance and Service Culture Based on Digital Platforms - Andayani, Nopi; Ali Ramdhani, Miftah Faiz (Indonesian Journal of Social Science Research, 2023)
Digital society is a reality of life in the 21st century where humans in various sectors of their lives are linked to digital technology. The era of digitalization refers to a description of the situation of changes in the lifestyle and behavior of individuals and organizations today. This is evidenced by the increase in internet users in Indonesia. During the Covid 19 pandemic, the use of the internet was used for online learning systems in elementary schools, middle schools, high schools and universities. Internet users are increasing rapidly. 2017 has reached 143.26 million people or equivalent to 54.68 percent of the total population of Indonesia. This number shows an increase of 10.56 million people from the survey results in 2016. 143.7 million people today and 202.6 million in 2021. The digital transaction value of IDR 203 t in 2019 Rp256t, 2020. IDR 403t in 2021 and IDR 530 t in 2022 (projection). The implications of using the internet and other social media in the learning process, shopping, and so on require rearrangement of the business service system; public services are increasingly facilitated on the one hand, and on the other hand, institutional arrangements and a new work culture need to be refined so that positive excesses can be increased and negative excesses can be reduced. The negative excesses of the transformation process resulted in cyberporn and cybercrime. The transformation process toward digital requires structuring talent and culture. The changes in the mindset and culture of the bureaucracy provide evidence of the increasing need for an agile paradigm in reforming the bureaucracy. However, it is realized that the challenges of implementing an agile paradigm are not easy. The bureaucracy is required to be able to create public services that are not one-size-fits-all but rather personalized. The way the public bureaucracy has been working has proven to be unable to produce innovative policies.